Analysis of Promotion, price, and Service Quality on Customer Satisfaction at PT. Amanu - Firmansyah, Satria Ramdhan; Murwanti, Sri (Jurnal Economic Resource, 2025)
This study's objective is to analyze the influence of Promotion, Price, and Service Quality on Customer Satisfaction at PT Amanu in Surakarta. This study's population is the community residing in the city of Surakarta. The study's sample consisted of 100 respondents with the criterion of respondents who had used the services of PT Amanu in the city of Surakarta. This study is quantitative in nature and uses primary data collected via Google Forms distributed surveys. Purposive sampling combined with non-probability sampling is the sample strategy employed in this investigation. Smart-PLS was used to examine the data. According to the study's findings, PT Amanu's customer satisfaction and promotions have a favorable and substantial relationship. At PT Amanu, price has a favorable and noteworthy impact on customer satisfaction. Customer satisfaction at PT Amanu is positively and significantly impacted by service quality.